How we measure poverty understates its extent and depth: Some results - Edita Abella Tan (University of the Philippines, School of Economics (UPSE), 2015)
The paper examined the methodology used for measuring the country's poverty line and poverty rate. It finds that the poverty line was not based on the cost of meeting an acceptable or minimum standard of living or of meeting basic needs by which to classify families as poor as is customarily done in other countries. The measure uses a simple construct referred to as subsistence poverty line to establish the overall poverty line. The subsistence poverty line is estimated to be the cost of food consumption of low-income families that meets their nutritional requirements. Thirty per cent of the subsistence poverty line is added to it to account for all non-food needs. The allotted budget for non-food needs is too low and not sufficient to meet the cost of all non-food basic needs. Consequently, the poverty line as measured does not meet all basic needs including food and underestimates the country's poverty rate. The underestimation of the poverty rate is seen in the higher rate of deprivation in particular basic needs such as housing, food consumption and education than the official poverty line. The paper concludes by recommending that the government gives high priority to slum clearance and housing program as a strategy for social and economic development. Housing for the poor has not been a priority of the government. So far only about 1% of the national budget goes to housing. At this time, the government has the resources to launch a massive housing program to eradicate the slums in five to ten years time. The paper cites existing and potential sources to finance a massive housing program. It cites the very successful housing program of Singapore and how it contributed to its sustained high rate of economic development.
Keywords: I32; 330; Measurement and analysis of poverty